Storing light near an exceptional point - Zhu, Yicheng; Hou, Jiankun; Geng, Qi; Xue, Boyi; Chen, Yuping; Chen, Xianfeng; Ge, Li; Wan, Wenjie (Nature communications, 2024)
Photons with zero rest mass are impossible to be stopped. However, a pulse of light can be slowed down and even halted through strong light-matter interaction in a dispersive medium in atomic systems. Exceptional point (EP), a non-Hermitian singularity point, can introduce an abrupt transition in dispersion. Here we experimentally observe room-temperature storing light near an exceptional point induced by nonlinear Brillouin scattering in a chip-scale 90-μm-radius optical microcavity, the smallest platform up to date to store light. Through nonlinear coupling, a Parity-Time (PT) symmetry can be constructed in optical-acoustical hybrid modes, where Brillouin scattering-induced absorption (BSIA) can lead to both slow light and fast light of incoming pulses. A subtle transition of slow-to-fast light reveals a critical point for storing a light pulse up to half a millisecond. This compact and room-temperature scheme of storing light paves the way for practical applications in all-optical communications and quantum information processing. Exceptional point introduces the ability to control and tune light propagation. Here the authors demonstrate a 90-μm-radius optical microcavity to store light, induced by nonlinear Brillouin scattering at room temperature.